2022
DOI: 10.3389/fimmu.2022.816634
|View full text |Cite
|
Sign up to set email alerts
|

A Coarse-Grained Model of Affinity Maturation Indicates the Importance of B-Cell Receptor Avidity in Epitope Subdominance

Abstract: The elicitation of broadly neutralizing antibodies (bnAbs) is a major goal in the design of vaccines against rapidly-mutating viruses. In the case of influenza, many bnAbs that target conserved epitopes on the stem of the hemagglutinin protein (HA) have been discovered. However, these antibodies are rare, are not boosted well upon reinfection, and often have low neutralization potency, compared to strain-specific antibodies directed to the HA head. Different hypotheses have been proposed to explain this phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 74 publications
2
2
0
Order By: Relevance
“…Our findings here and earlier [18] complement a recent computational study that identifies the stalk domain as immunosubdominant due to the steric inability to recruit bivalently binding B-cell receptors [17]. Hindered accessibility of the conserved stalk covered by the glycan shield interferes with the development of broadly immunizing stalk antibodies.…”
Section: Plos Computational Biologysupporting
confidence: 77%
See 2 more Smart Citations
“…Our findings here and earlier [18] complement a recent computational study that identifies the stalk domain as immunosubdominant due to the steric inability to recruit bivalently binding B-cell receptors [17]. Hindered accessibility of the conserved stalk covered by the glycan shield interferes with the development of broadly immunizing stalk antibodies.…”
Section: Plos Computational Biologysupporting
confidence: 77%
“…Recently, a structural investigation found that RBD-ACE2 binding affinity of the Omicron variant is similar to the Delta variant, and that Omicron spike displays significant antibody evasion [14], in line with earlier studies [1,2,15,16]. Ovchinnikov & Karplus used a kinetic model of B-cell affinity maturation to determine the importance of bivalent versus monovalent antibody-antigen interactions in vaccination and infection [17].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Two schools of thought have since arisen to overcome the aforementioned challenges presented by hm-IDPs: universal vaccines and personalized medicine. Progress towards universal vaccines continues to advance every year, with increasingly informed design rules on how to elicit antibodies that target conserved aspects of viral machinery ( 7 14 ). Much of this newfound knowledge has come from studying crystal structures of broadly neutralizing antibodies (bnAbs)—which neutralize diverse viral strains by targeting conserved regions on hm-IDP surface proteins—and attempting to reconstruct the evolutionary pathways of these bnAbs ( 15 26 ).…”
Section: Introductionmentioning
confidence: 99%